Pre-Service English Teachers’ Insights on Using Zep Quiz as a Learning Tool in EFL Classrooms - Tiodora, Lucia; Imaniar, Fahmy; Susanti, Effi (IKIP Siliwangi, 2026)
This study investigates the perspectives of pre-service English teachers on the use of Zep Quiz in the context of EFL (English as a Foreign Language) instruction. Along with the development towards the digital era, integrating technology in educational settings is crucial, especially for future educators looking to employ technology based methods to create engaging and appealing lessons. Employing a qualitative approach with exploratory descriptive methods, this study examines English education students at UIN Sunan Ampel Surabaya who implemented Zep Quiz during their internship teaching practice. Data collection involved semi-structured interviews, observations, and documentation, followed by thematic analysis. Findings reveal that Zep Quiz was user friendly and effective in enhancing student motivation and engagement. Gamification features such as scoring and leaderboards fostered a competitive and enjoyable learning environment. However, challenges related to technological limitations were also found, such as connectivity issues and device limitations among students. The study highlights the importance of teacher education focusing on technology mastery and classroom management skills to address such challenges. The results are anticipated to influence pre-service English teacher education programs, particularly in the integration of technology in EFL instruction.